Kierunki przeznaczania wpływów z tytułu opłat i podatków ekologicznych - Ptak, Michał (The way of using the revenue from environmentally related charges and taxes, 2006)
The paper presents possible ways of using the revenue from environmentally related charges and taxes. These funds may be paid into general governmental budget and added to the other revenues of the government. Alternatively, the revenues may be earmarked for specific purposes, some of which may be environmental, especially by setting up funds or mechanisms for reallocating the revenue to environmental protection programmes. The latter option is often chosen for reasons of political feasibility and acceptance but it also entails many drawbacks. The author presents the advantages and disadvantages of this solutio
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 156-167